Blood count to determine chronic inflammation severity in obese adolescents - Martini Wongkar; Handoko Lowis; Sarah M. Warouw; Julius Lolombulan; Stefanus Gunawan (Indonesian Pediatric Society, 2020)
Background Obesity is a growing public health problem of rapidly increasing prevalence in developing countries. Chronic low-grade inflammation plays a key role in the pathophysiology of obesity. Blood count values and ratios have been used as markers of inflammatory diseases. These parameters may be useful to determine the severity of chronic inflammation in obese children. Objective To determine if red blood cell distribution width (RDW), neutrophil-to-lymphocyte ratio (NLR), mean platelet volume (MPV), platelet distribution width (PDW), and platelet-to-lymphocyte ratio (PLR) can be useful for determining the severity of chronic inflammation in obese children. Methods This observational, analytic study was conducted in obese adolescents aged 14-18 years at senior high schools in Manado, North Sulawesi, from July to September 2018. Students with congenital anomalies, autoimmune diseases, history of asthma, or malignancy were excluded. Pearson’s correlation was used to analyze for potential relationships between obesity and red blood cell distribution width (RDW), neutrophil-to-lymphocyte ratio (NLR), mean platelet volume (MPV), platelet distribution width (PDW), and platelet-to-lymphocyte ratio (PLR). Results There was a negative relationship between obesity and MPV, but it was not statistically significant (r=-0.006; P=0.485). There were positive, but not significant relationships between obesity and RDW (r=0.139; P=0.192), NLR (r=0.155; P=0.166), PDW (r=0.02; P=0.45), and PLR (r=0.146; P=0.181). Conclusion The RDW, NLR, MPV, PDW, and PLR values are not significantly associated with severity of obesity in adolescents.